Whole genome sequencing informs SNP-based breeding strategies to safeguard genetic diversity in captive African lions - Chen, Wanzhao; Xing, Ronghe; Xia, Panpan; Yang, Yujie; Ma, Chao; Xia, Lining (Frontiers in Veterinary Science, 2025)
IntroductionAfrican lions (Panthera leo) face severe population declines, making captive breeding programs essential for conservation. However, genetic data scarcity in such programs elevates inbreeding risks and threatens genetic diversity.MethodsUsing next-generation sequencing (NGS), we analyzed genome-wide genetic markers from 10 captive African lions at Xinjiang Tianshan Wildlife Park. We identified high-confidence SNPs, evaluated population structure, and calculated kinship/inbreeding coefficients alongside identity by descent (IBD) and identity by state (IBS) analyses.ResultsWe identified 5,051,795 high-confidence SNPs. The population contained distinct genetic subgroups. Six lion pairs exhibited elevated kinship coefficients, with one individual showing inbreeding signs. We developed a science-driven breeding program based on population genetic structure, identity by descent (IBD) analysis, and Identity by State (IBS) analysis. This program prioritizes pairings with low kinship while maintaining a balanced ancestral lineage.DiscussionThis study underscores the importance of genomic tools in managing captive populations, offering actionable insights to mitigate inbreeding risks and improve long-term viability. This approach offers a model for optimizing breeding strategies in other endangered species conservation efforts.